2003
DOI: 10.4049/jimmunol.171.5.2366
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Mediate NK Cell Help for Th1 and CTL Responses: Two-Signal Requirement for the Induction of NK Cell Helper Function

Abstract: Early stages of viral infections are associated with local recruitment and activation of dendritic cells (DC) and NK cells. Although activated DC and NK cells are known to support each other’s functions, it is less clear whether their local interaction in infected tissues can modulate the subsequent ability of migrating DC to induce T cell responses in draining lymph nodes. In this study, we report that NK cells are capable of inducing stable type 1-polarized “effector/memory” DC (DC1) that act as carriers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
302
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 330 publications
(323 citation statements)
references
References 75 publications
14
302
0
1
Order By: Relevance
“…On the one hand, NK-DC crosstalk is characterized by the capacity of activated NK cells to induce DC maturation with elevated IL-12p70 production and subsequently an increased capacity to induce Th1 and CTL responses [9]. This NK-induced DC maturation depends at least in part on soluble factors such as TNF-a [10] and IFN-g [11] as well as on engagement of the natural cytotoxicity triggering receptor 30 [12].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, NK-DC crosstalk is characterized by the capacity of activated NK cells to induce DC maturation with elevated IL-12p70 production and subsequently an increased capacity to induce Th1 and CTL responses [9]. This NK-induced DC maturation depends at least in part on soluble factors such as TNF-a [10] and IFN-g [11] as well as on engagement of the natural cytotoxicity triggering receptor 30 [12].…”
Section: Introductionmentioning
confidence: 99%
“…The two-signal requirement for the induction of NK ''helper'' activity was met by using freshly isolated NK cells in the presence of an additional costimulatory signal. 7,16 The presence of IFN-c (which can be induced by TLR ligands) during DC maturation overcomes maturation-associated DC 'exhaustion', yielding stable type 1-polarized DCs that produce higher levels of IL-12p70 and exhibit a dramatically enhanced capacity to induce Th1 responses. 26 It has been reported that IFN-c is produced by NK cells after 17 h of stimulation with poly(I:C), and it peaks at 48 h. 27 In our study, the level of IFN-c production in resting NK cells after 48 h of stimulation in the presence of TLR agonists and cytokines was higher than that observed in either activated NK cells or resting NK cells in the absence of costimulatory signals.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not detect any significant killing of DCs by resting NK cells or activated NK cells, it is possible that depending on the cytolytic activity of activated NK cells, the DC/NK cell ratio or the presence of particular NK cell subsets, NK cells will mainly kill or inactivate DCs, resulting in suppression of the immune response. 7 The key to the initiation of immune responses to pathogens is the recognition of pathogen associated ligands that are not normally expressed by host cells. This recognition is mediated by members of the TLR family, several of which are expressed by immature DCs 28 and NK cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations